(3TQM bUjOI HOQ GdOjf GdeQGOis - (3CHh MGeO GdMSjfj Gdecj Hf eMeO Hf Ydj GdHWGhQis; (3GdMSf Hf bGSe Hf YHO Gddg GdeQGOj GdeUQj, CHh eMeO, HOQ GdOjf, GdeYQha HGHf Ce bGSe,J (B749 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi OQC GdNdGFb EfYGekG hEMSGfkG CeG HYO Efg bO WdH efi HYV fLHGA GdWdHI TQM bUjOI HOQ GdOjf Hf bGSe GdeQGOi GdeTJedI Ydi HYV eG GJab NWg hGNJda eYfGg hGdJbOe bHd GdTQhY ai GdebUhO GdJYQja HGdfGXe s
(3BNQgG (B:s
(3hcKjQ ef GdfGS MUd dg GdRgO ai GdeMHhH hGdeYThb hgPG cKjQ ai CTYGQ GdfGS hfKQge hdfbJUQ Ydi gPG dGbOQ defGSHJg hdfNJe gPG GdTQM CHjGJ ef bUjOI CHj ESMGb GdCdHjQi defGSHJgG dHjJ GdfXGe hdjcf NJGe gPG GdJbjjO hGdMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs